2017
DOI: 10.1002/hon.2439_166
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine Plus Liposomal Doxorubicin for Relapsed Refractory T‐cell Lymphomas

Abstract: Results: Nine cases of Alk + LBCL, which were diagnosed over a period of 6 years (2012)(2013)(2014)(2015)(2016)(2017), were studied. Out of 9 patients, 7 were male and 2 were female with median age of 51 yr (age range: 14 to 63 yrs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Subsequently, a phase II trial of LD 20 mg/m 2 every 2 weeks for 8 cycles followed by bexarotene reported an ORR of 41% at 16 weeks (18). LD has also been evaluated in patients with TCL, including PTCL, in combination with gemcitabine with modest results (19).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a phase II trial of LD 20 mg/m 2 every 2 weeks for 8 cycles followed by bexarotene reported an ORR of 41% at 16 weeks (18). LD has also been evaluated in patients with TCL, including PTCL, in combination with gemcitabine with modest results (19).…”
Section: Introductionmentioning
confidence: 99%